Principles，technologies and challenges of OQAM-OFDM for 5G applications - Jun LI; Yuan TIAN; Yu QIU; Da CHEN; Tao JIANG (Dianxin kexue)
5G will need to be able to support much larger connections of communication devices and meet the requirements of diverse scenarios.However，this requirement cannot be met by OFDM（orthogonal frequency division multiplexing）due to its own drawbacks.As an alternative approach to OFDM，OQAM-OFDM （offset quadrature amplitude modulation based orthogonal frequency division multiplexing）adopts a prototype filter that is well localized in frequency domain，which makes OQAM-OFDM quite suitable for 5G.The OQAM-OFDM system was briefly introduced，then，its superiority employed in 5G was deeply discussed.Finally，some key technical issues of OQAM-OFDM for application in 5G were summarized，such as tail shortening.